Activation of GABAB Receptor Suppresses Diabetic Neuropathic Pain through Toll-Like Receptor 4 Signaling Pathway in the Spinal Dorsal Horn - Liu, Peng; Yuan, Hong-Bin; Zhao, Shuang; Liu, Fei-Fei; Jiang, Yu-Qing; Guo, Yue-Xian; Wang, Xiu-Li (Mediators of Inflammation, 2018)
Diabetic neuropathic pain (DNP) is a prevalent complication in diabetes patients. Neuronal inflammation and activation of Toll-like receptor 4 (TLR4) are involved in the occurrence of DNP. However, the underlying mechanisms remain unclear. Downregulation of gamma-aminobutyric acid B (GABAB) receptor contributes to the DNP. GABAB receptor interacts with NF-κB, a downstream signaling factor of TLR4, in a neuropathic pain induced by chemotherapy. In this study, we determined the role of TLR4/Myd88/NF-κB signaling pathways coupled to GABAB receptors in the generation of DNP. Intrathecal injection of baclofen (GABAB receptor agonist), LPS-RS ultrapure (TLR4 antagonist), MIP (MyD88 antagonist), or SN50 (NF-κB inhibitor) significantly increased paw withdrawal threshold (PWT) and paw withdrawal thermal latency (PWTL) in DNP rats, while intrathecal injection of saclofen (GABAB receptor blocker) decreased PWT and PWTL in DNP rats. The expression of TLR4, Myd88, NF-κBp65, and their downstream components IL-1 and TNF-α was significantly higher in the spinal cord tissue in DNP rats compared to control rats. Following inhibition of TLR4, Myd88, and NF-κB, the expression of IL-1 and TNF-α decreased. Activation of GABAB receptors downregulated the expression of TLR4, Myd88, NF-κBp65, IL-1, and TNF-α. Blockade of GABAB receptors significantly upregulated expression of TLR4, Myd88, NF-κBp65, IL-1, and TNF-α. These data suggest that activation of the TLR4/Myd88/NF-κB signaling pathway is involved in the occurrence of DNP in rats. Activation of GABAB receptor in the spinal cord may suppress the TLR4/Myd88/NF-κB signaling pathway and alleviate the DNP.